Characterization of Zinc Oxide Nanolaminate Films - Oleson, B.J.; Bilke, L. M.; Krueger, J. S.; King, S. T. (Proceedings of the Wisconsin Space Conference, 2011)
This project sought to increases the understanding of fundamental properties of the transparent conducting oxide materials needed to improve solar energy device efficiency. Specifically, this study focused on the development of Cu:ZnO nanolamintate materials where Cu and ZnO form alternating layers on the nanomerter scale. Initial results show no intermixing of materials, and suggest that these nanolaminates may be employed as infrared mirrors.Â